A Two-Step Method for the Synthesis of Massively-Thinned Large Planar Arrays - Wang, Xin-Kuan; Wang, Gui-Bao (2018 Cross Strait Quad-Regional Radio Science and Wireless Technology Conference (CSQRWC), 2018)
a two-step method is proposed to address the low sidelobe synthesis of the massively-thinned large planar array (MTLPA). In the first step, an MTLPA is obtained with well-behaved sidelobe performance through performing the iterative Fourier transform (IFT). Thanks to the high convergence of the IFT, this operation just require a few seconds CPU-time. Furthermore, in the second step, a total of 100 elements within the MTLPA that spaced greater than half wavelength are selected, and their locations are further optimized by the algorithm of differential evolution (DE) to decrease the sidelobe level. Some numerical results indicate that the proposed method can reduce the sidelobe level of the thinned array by at least 1.3dB, as is compared to the published reports.